Cubic PbGeO3 perovskite oxide: A compound with striking electronic, thermoelectric and optical properties, explored using DFT studies - Dey, Aditya; Sharma, Ramesh; Dar, Sajad Ahmad; Wani, Inamul Haq (Computational Condensed Matter, 2021)
An in-detail study of cubic structured perovskite oxide, PbGeO3 has been performed using first principles calculations to speculate its structural, electronic, thermoelectric and optical characteristics. We have employed different exchange functionals to accurately compute these mentioned properties. We have studied the physical properties first by carrying out optimization using different methods. Thereafter, we observed that the nmBJ-GGA (new modified Becke−Johnson GGA) approach gave us the most enhanced electronic structures. The electronic properties suggest that this compound is an indirect semiconductor. Using this means only, we further computed the thermoelectric (TE) and optical properties. The high figure of merit and power factor both at low and high temperatures shows its thermoelectric efficacy and generates a prospect to use this compound for various TE transport applications. Moreover, the optical properties show diverse and contrasting behaviour depending on the range of photon energy or regions of electromagnetic spectrum. On further inspection, it is revealed that such assorted optical response can enable cubic PbGeO3 to be used in making optical devices, solar cells and fields like optoelectronics. •The electronic, thermoelectric & optical properties of cubic PbGeO3 perovskite oxide are studied via DFT calculations.•Different exchange functionals are employed to accurately compute the properties.•It behaves as a moderate gap semiconductor having excellent thermoelectric properties and contrasting optical behavior.•Our study shows they can be potentially used as energy harvesting material, in solar cells, in optoelectronic devices, etc.